Advances in the characterization of three coffee varieties in Lodana parish, Santa Ana – Manabí - Cañarte García, Horley (2024)
The present study aims to evaluate the advances in the characterization of three coffee varieties in Lodana Parish, Santa Ana Canton, Manabí Province. The specific objectives include analyzing the behavior of the varieties under local climatic conditions, determining the productivity of each, and identifying the varieties most susceptible to diseases that may affect the crop. Coffee is one of the country's main agricultural activities, ranking among the top ten in cultivated areas and grown in almost all provinces. For this purpose, a Completely Randomized Block Design (CRBD) with three replications was used, and each experimental unit consisted of 50 plants of the Arabica coffee varieties: Sachimor, Manabí 01, and Typica. The study included a population of 450 plants, planted at a spacing of 1.30 meters between plants and 2 meters in rows, over a duration of two years, allowing for reliable data collection. The results show that the varieties best adapted to the soil and climatic conditions of the area were Sachimor and Manabí 01. Among them, the Sachimor variety stood out for its higher productivity, reaching a production of 15,585 grams. On the other hand, despite being native to the region, the Typica variety showed a significantly lower yield.